Response of onion to different nitrogen levels and method of transplanting in moderately salt affected soil - Khalil Ahmed; Muhammad Qaisar NAWAZ; Syed Saqlain HUSSAIN; Muhammad RIZWAN; Muhammad SARFRAZ; Ghulam Mustafa WAINSE; Muhammad JAMIL (Acta Agriculturae Slovenica)
Rapid increase in population and consumption, urged upon the agronomists to develop a comprehensive site specific agro technology to boost up production per unit area and quality of daily dietary onion crop in salt affected soils by improving some basic components of the prevailing onion production technology in Pakistan. In this perspective a detailed and systematic series of field studies were undertaken for three consecutive years (2013 -  2015) at Soil Salinity Research Institute, Pindi Bhattian, Pakistan to evaluate different nitrogen levels and the cost-effective planting technique for onion production under salt affected conditions. The experiment was laid out in split plot arrangement using randomized complete block design having three replications. Two planting methods, ridge and bed planting and 4 nitrogen levels, 1- recommended dose (RD) of N (90 kg ha-1), 2 -75 % N of RD (67.5 kg ha-1), 3 -125 % N of RD (112.5 kg ha-1), 4 - 150 % N of RD (135 kg ha-1) were used. Planting methods were kept in main plots and nitrogen levels in sub plots keeping sub-plot size of 4 m x 6 m. Measurements included were: plant height, number of leaves/plants/m-2, bulb diameter, bulb mass, total bulb yield, number of flowers/umbel, seed mass/plant and 1000-seed mass. Results showed that maximum onion yield and yield attributes were recorded with nitrogen application at rate of 150 & 125 of RD in ridge planting. However nitrogen application at rate of 125 of RD in ridge planting recorded higher economic returns over all the other treatments and is recommended as most cost effective technique for onion production under salt affected soil as compare to other treatments.